Is Resistance to Dolutegravir Possible When This Drug Is Used in First-Line Therapy? - Thibault Mesplède; Mark A. Wainberg (Viruses, 2014)
Dolutegravir (DTG) is an HIV integrase inhibitor that was recently approved for therapy by the Food and Drug Administration in the United States. When used as part of first-line therapy, DTG is the only HIV drug that has not selected for resistance mutations in the clinic. We believe that this is due to the long binding time of DTG to the integrase enzyme as well as greatly diminished replication capacity on the part of viruses that might become resistant to DTG. We further speculate that DTG might be able to be used in strategies aimed at HIV eradication.